WHAT KIND OF PHILOSOPHY UNDERLIES THE FUTURE CURRICULUM FOR INDONESIA? - Ida Bagus Ari Arjaya; I Wayan Suastra; Desak Nyoman Budiningsih; I Made Surya Hermawan (Unmas Press, 2022)
Nowadays, there are many educational problems experienced by the education system in Indonesia. The educational problem that is most clearly seen as an evaluation of the learning process is the problem of learning outcomes for Indonesian students in Trends in International Mathematics and Science Study (TIMSS) and Program for International Student Assessment (PISA). In terms of developing the personality or character of students, problems with disciplinary action, juvenile delinquency, honesty, and so on still adorn Indonesian education today. Educators must shape the character of students based on their local potential. The local potential can be in the form of local wisdom that forms a positive attitude of students in order to survive in the 21st-century competition. Seeing the problems that have been previously disclosed, the world of education in Indonesia actually needs to redefine the educational philosophy that underlies its curriculum to meet future curriculum needs. The results of qualitative descriptive research show 1) that the philosophical schools that underlie education are idealism, perennialism, reconstructionism, essentialism, progressivism, pragmatism, realism, materialism, and existentialism, 2) Philosophy for the current curriculum is related to the current curriculum. which is related to the independent learning curriculum and the independent campus is closely related to the philosophy of progressivism and materialism, 3) While the philosophical schools that underlie the future curriculum are the idealism, pragmatism, and humanist philosophy of Ki Hajar Dewantara